2020
DOI: 10.1016/j.ijso.2020.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Practice of spinal anesthesia among anesthetists in the operation room of referral hospital: Cross-sectional study

Abstract: Background: spinal anesthesia is easy to access, cheap safe for surgery done below umbilicus but it has a lot of complications like total spinal, high spinal, hypotension and sever neurological abnormality due to in adequate preparation and poor practice while administration spinal anesthesia in the operation theatres. This audit was aimed to improve practice of spinal anesthesia in our theatre meet the audit standards or not. Methods: This audit was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Similarly, a study done at the University of Gondar by Ferede YA et al, 2020 found the assessment of patient's emotional reaction and pain during injection, check patient's pulse rate and blood pressure immediately after spinal anesthesia, and appropriate positioning of the patient was not completely practiced and they recommend for improvements. 35 Another study conducted at the University of Gondar by Chekol W et al, 2018 found as all anesthetists did not wash their hands and wear sterile gowns throughout the procedure which is inline with our study. 36 In conflicting with our finding's various literature and clinical practice guidelines reported and recommended that while performing this spinal nerve block, it is vital to completely practice the standards of spinal anesthesia to ensure patient safety and enhance the better outcome.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similarly, a study done at the University of Gondar by Ferede YA et al, 2020 found the assessment of patient's emotional reaction and pain during injection, check patient's pulse rate and blood pressure immediately after spinal anesthesia, and appropriate positioning of the patient was not completely practiced and they recommend for improvements. 35 Another study conducted at the University of Gondar by Chekol W et al, 2018 found as all anesthetists did not wash their hands and wear sterile gowns throughout the procedure which is inline with our study. 36 In conflicting with our finding's various literature and clinical practice guidelines reported and recommended that while performing this spinal nerve block, it is vital to completely practice the standards of spinal anesthesia to ensure patient safety and enhance the better outcome.…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, a study done at the University of Gondar by Ferede YA et al, 2020 found the assessment of patient’s emotional reaction and pain during injection, check patient’s pulse rate and blood pressure immediately after spinal anesthesia, and appropriate positioning of the patient was not completely practiced and they recommend for improvements. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Majority of the participants were male 48(80%). The median working experience of the participants was 15 years (IQR): (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) with no significant difference between both the genders (mean: 17.2 vs 13.8, p=0.277). Additionally, results showed that more than half of the participants 33(55.5%) had professional experience of ≥15 years.…”
Section: Resultsmentioning
confidence: 99%
“…Needle gauge applied in majority of the participants of the current study was 25 gauge. Studies reports incidences of PDPH as 5% with 26 G and 8.7% for cutting needles of 25G Quincke) whereas 4%, 2.8%, and 3.1% for three pencil point needles (24G GM, 24G Sprotte, 25G Whitacre) respectively 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…The educational videos were mostly uploaded by NYSORA and Ultrasound for Regional Anesthesia (URSA). These websites are well-organized with highly accurate educational content; novice trainees can learn basic anatomy and clinical skills for UGRA from NYSORA and URSA [55][56][57][58][59][60][61]. We observed several common features in all videos; (1) the BSQS lacked the equipment preparation and post-procedure information and (2) there were very few comments (1.38 ± 3.15 (median: 0)).…”
Section: Discussionmentioning
confidence: 99%